Redox switching of an artificial transmembrane signal transduction system. Issue 17 (22nd February 2021) - Trevisan, Lucia; Kocsis, Istvan; Hunter, Christopher A.
Abstract : An external redox signal delivered by ascorbic acid was used to trigger membrane translocation in a synthetic transduction system. Abstract : Transmission of chemical signals across lipid bilayer membranes can be achieved using membrane-anchored molecules, where molecular motion across the bilayer is controlled by switching the polarity of two different head groups. An external redox signal delivered by ascorbic acid was used to trigger membrane translocation in a synthetic transduction system.